Sustaining social harmony in diverse schools: A structural functionalist analysis of school climate using the AGIL framework - Wahyu Ilham Wahyu; Erianjoni; Isnarmi Moeis; Eka Asih Febriani (Program Pascasarjana Universitas Negeri Yogyakarta, 2026)
This study aims to analyze how school climate functions in maintaining social harmony amid diversity at SDN 32 Muaro Putuih through the lens of structural functionalism, particularly Talcott Parsons’ AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). The research employs a qualitative approach with a case study design to explore school climate as a lived social reality experienced by school members. Data were collected through non-participant observation, in-depth semi-structured interviews, and documentation involving school principals, teachers, students, parents, and community members. The validity of the data was ensured through source and time triangulation, while data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that school climate functions as a social system that fulfills AGIL requirements: (1) adaptation is reflected in inclusive practices accommodating religious, ethnic, and linguistic diversity; (2) goal attainment is shown through the shared commitment to sustaining social harmony; (3) integration is achieved through mutual trust, respect, and effective communication among school members; and (4) latency (pattern maintenance) is maintained through the continuous internalization of tolerance, empathy, and social care in everyday interactions. A positive relational school climate characterized by inclusive interactions and strong school–parent communication plays a crucial role in sustaining harmony. Diversity does not lead to conflict but is managed through daily social practices grounded in shared values and supportive leadership. These findings suggest that school climate, as a socially constructed system, significantly contributes to fostering inclusive and harmonious relationships in diverse educational settings while simultaneously demonstrating the functional operation of AGIL in maintaining social order.